Managing Momentum in Climate Negotiations - Stefano Carattini; Andreas Löschel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The Conference of the Parties (COP) has proven a valuable outlet to advance the climate agenda. The combination of high media coverage, extremely high expectations set by influential environmentalists, and unanimity rules has, however, started to limit its effectiveness. Technical issues can legitimately require years to be addressed. Delays on such issues should not lead society to ignore progress in other areas. If anything, defining expectations based on technical issues creates more incentives for unwilling countries to delay action and spread pessimism. The coronavirus is bad news for climate action, but also provides opportunities. The absence of a session of the COP in 2020 gives negotiators additional time to address technical issues behind the scenes, including through club approaches. Virtual forums can be used to increase interactions, also involving top diplomats. The extra time also allows global leaders and influential environmentalists to improve their communication strategies, increasing ambition while effectively managing momentum.
Keywords: D71; D84; F53; Q54; 330; international environmental agreements; cooperation; beliefs; climate change